Fighting for climate environmental education in Brazil: educommunicative perspectives against the instrumentalization of human and nonhuman lives - Brianezi, Thaís; Tate, Joanne Christine Marras (Frontiers in Communication, 2025)
Brazilian socio-environmental coalitions and movements that fight for climate environmental education have invested in educommunicative practices and perspectives against the instrumentalization and over-exploitation of human and nonhuman lives over the years. They seem to have learned that, to postpone the end of worlds it is necessary to always tell one more story. Aílton Krenak, Indigenous leader and Brazilian philosopher, teaches us that it is increasingly important to ask ourselves by whom and where these narratives emerge and toward what futures they point at. In this conceptual analysis article, we follow Krenak and ask what stories are being told about environmental communication in the Global South, specifically Brazil, and what futures we want to follow as environmental communication scholars. Following a literature review and empirical data on the recent Brazilian social mobilizations in favor of climate environmental education, we first analyze how the challenge of overcoming economic conceptions of development goes along with overcoming the instrumental vision of communication. We then discuss four epistemological tensions that challenge environmental communication in this counter-hegemonic movement: tactical and strategic, complexity and reduction, virtuality and grounding, and ancestry and acceleration. Finally, we then demonstrate how educommunication, an epistemology of the South, contributes to the decolonial process of paradigmatic rupture of communication, guided by more plural perspectives such as good living (buen vivir).